Spinal Cord Stimulation Alleviates Sensitization of Neuropathic Pain by Upregulating G Protein-Coupled Receptors to Inhibit Overexpression of Cav2.2 and Its Downstream Excitatory Neurotransmitters - Liu SL; Zhang HE; Kang JY; Ji HY; Cai ZH; Qi SH; Liu SS; Zhou HC (Journal of Pain Research)
Si-Liang Liu,1,2 Hong-En Zhang,2,3 Ji-Yu Kang,2,3 Huai-Yu Ji,3 Zhen-Hua Cai,4 Si-Hua Qi,1 Shan-Shan Liu,3 Hua-Cheng Zhou2,3 1Department of Anesthesiology, the Fourth Affiliated Hospital of Harbin Medical University, Harbin, Heilongjiang, 150001, People’s Republic of China; 2NHC Key Laboratory of Molecular Probes and Targeted Diagnosis and Therapy, Harbin Medical University, Harbin, 150001, People’s Republic of China; 3Department of Pain Management, the Fourth Affiliated Hospital of Harbin Medical University, Harbin, Heilongjiang, 150001, People’s Republic of China; 4Department of Pain Management, The Second Affiliated Hospital of Harbin Medical University, Harbin, Heilongjiang, 150086, People’s Republic of ChinaCorrespondence: Hua-Cheng Zhou, Department of Pain Management, The Fourth Affiliated Hospital of Harbin Medical University, 37 Yiyuan Street, Harbin, Heilongjiang, 150001, People’s Republic of China, Email zhouhuacheng@hrbmu.edu.cnPurpose: Spinal cord stimulation (SCS) is an effective treatment for various forms of neuropathic pain (NP), including postherpetic neuralgia, phantom limb pain, and painful diabetic neuropathy. Currently, although there have been studies on the analgesic mechanisms associated with SCS, the roles of ion channels in the therapeutic effects of SCS are still unclear.Methods: In this study, NP hyperalgesia was induced in a rat model using chronic constriction injury (CCI) of the sciatic nerve. Ten days after modeling, the rats were treated with SCS (50 hz, 200 μs, and 80% motor threshold) for 3 hours each day for 5 consecutive days. The role of ion channels in SCS-induced analgesia was investigated using bioinformatics, western blotting, and immunofluorescence assays.Results: Behavioral analysis showed that SCS treatment for 5 consecutive days increased both the mechanical and thermal pain thresholds of the CCI rats. The bioinformatics results indicated that N-type calcium channels (Cav2.2) were key in the induction of NP-associated hyperalgesia, with the opioid receptor-like 1 receptor (ORL-1) functioning as an upstream inhibitor of Cav2.2. The results also showed that SCS induced analgesia through upregulation of ORL-1 to inhibit overexpression of Cav2.2 and its downstream neurotransmitters, substance P and glutamate. This analgesic effect could be reversed by both Cav2.2 agonists and ORL-1 inhibitors.Conclusion: SCS alleviates hyperalgesia in NP through upregulation of ORL-1 to inhibit the overexpression of Cav2.2 and its downstream neurotransmitters. This may be one of the mechanisms through which SCS induces analgesia. The elucidation of the ion channel mechanism of SCS will improve the clinical application procedures of SCS.Keywords: Neuropathic pain, Pain sensitization, Spinal cord stimulation, N-type calcium channels, Glutamate, Substance P